The SIP protocol update: Eight strategies, incorporating Rapid Peripheral Vein Assessment (RaPeVA), to minimize complications associated with peripherally inserted central catheter insertion - Brescia, Fabrizio; Pittiruti, Mauro; Spencer, Timothy R; Dawson, Robert B (The journal of vascular access, 2024)
Insertion of Peripherally Inserted Central Catheters (PICCs) is potentially associated with the risk of immediate/early adverse events, some of them minimal (repeated punctures) and some relevant (accidental arterial puncture or nerve-related injury). Several strategies adopted during the insertion process may minimize the risk of such events, including late complication risks such as infection, venous thrombosis, or catheter dislodgment and/or malposition. This paper describes an update version of the SIP protocol (Safe Insertion of PICCs), an insertion bundle which includes eight effective strategies that aims to minimize immediate, early, or late insertion-associated complications. These strategies include: preprocedural ultrasound assessment utilizing the RaPeVA (Rapid Peripheral Venous Assessment) protocol; appropriate skin antiseptic technique; choice of appropriate vein, adoption of the Zone Insertion Method™; clear identification of the median nerve and brachial artery; ultrasound-guided puncture; ultrasound-guided tip navigation; intra-procedural assessment of tip location; correct securement of the catheter, and appropriate protection of the exit site. This updated version of the SIP protocol includes several novelties based on the most recent evidence-based scientific literature on PICC insertion, such as the clinical relevance of the tunneling technique, the use of ultrasound for intra-procedural tip navigation and tip location, and the new technologies for the protection of the exit site (cyanoacrylate glue) and for the securement of the catheter (subcutaneous anchorage).